A Short Synthesis of Clionamine D. Issue 11 (28th October 2015) - Hao, Xiang; Wu, Jingjing; Tian, Hailong; Shi, Yong; Lin, Jingrong; Tian, Weisheng
Abstract: Herein we describe a scalable four‐step preparation of α ‐methylene‐ γ ‐lactone3 from steroidal sapogenin. This method allowed a facile synthesis of clionamine D, a natural aminosteroid with potent autophagy bioactivity and unprecedented chemical structure. Abstract : A convenient preparation of α ‐methylene‐ γ ‐lactone3 from tigogenin was developed, which enabled an efficient synthesis of clionamine D, a natural aminosteroid with the autophagy bioactivity and anunprecedented spirobislactone structure.